Evaluation of mechanical and electrochemical properties of FHA-coated Co–Cr implant. Issue 2 (2nd February 2017) - Shirdar, Mostafa Rezazadeh; Izman, Sudin; Kheimehsari, Hirbod Maleki; Ahmad, Norhayati; Ma'aram, Azanizawati
Abstract : In this study, hydroxyapatite (HA) and fluoridated hydroxyapatite (FHA) as a comparison were deposited electrophoretically on a cobalt (Co)–chromium (Cr)-based implant to increase its surface bioactivity and reduce ion release. The coated substrates were then sintered at 650°C for 1 h. Typical apatite structures were obtained for both coatings after electrophoretic deposition and subsequent post-treatment. The morphology of the coated layers was characterised using field emission scanning electron microscopy and energy-dispersive spectroscopy. Mechanical properties of the coated layers including adhesion strength and Vickers microhardness were examined. In addition, the electrochemical corrosion behaviour of the FHA-coated substrate was evaluated in simulated body fluid solution and compared to uncoated as well as HA-coated samples. The results indicate that FHA coating has a denser structure compared to the HA-coated layer, resulting in the improvement of mechanical properties as well as corrosion resistance. Furthermore, immersion test findings reveal that FHA coated Co–Cr shows lower Cr ion release after 1, 7, 14 and 21 d of immersion as compared to the HA-coated implant.